2014
DOI: 10.13073/fpj-d-13-00051
|View full text |Cite
|
Sign up to set email alerts
|

Composite Flooring Quality of Combined Wood Species Using Adhesive from Merbau Wood Extract

Abstract: Polyphenol chemical components extracted from merbau (Intsia spp.) wood exhibit a strong affinity for resorcinol and formaldehyde in alkaline conditions, forming a copolymer that could serve as an adhesive. A liquid extract of merbau wood (M) was allowed to copolymerize with resorcinol (R) and formaldehyde (F) under alkaline conditions, with an M:R:F weight ratio of 100:5:10. The course of the reaction and potential mechanisms of copolymerization were scrutinized using Fourier transform infrared spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 1 publication
4
12
0
7
Order By: Relevance
“…The results of the UV-visible analysis in this study are presented in Fig. 1 Figure 1 shows that the liquid extract of merbau wood (λ=279 nm) consisted of conjugated or aromatic systems, similar to standard resorcinol (which was used as the reference), which had a wavelength (λ) of 274 nm. In previous work (Santoso et al 2014), similar spectra were found for different instruments of UV-vis spectroscopy. For example, the wavelength for merbau extractives (ME) was 279.5 nm, and the value was 273.5 for analytical resorcinol.…”
Section: Uv-vis Identificationsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of the UV-visible analysis in this study are presented in Fig. 1 Figure 1 shows that the liquid extract of merbau wood (λ=279 nm) consisted of conjugated or aromatic systems, similar to standard resorcinol (which was used as the reference), which had a wavelength (λ) of 274 nm. In previous work (Santoso et al 2014), similar spectra were found for different instruments of UV-vis spectroscopy. For example, the wavelength for merbau extractives (ME) was 279.5 nm, and the value was 273.5 for analytical resorcinol.…”
Section: Uv-vis Identificationsupporting
confidence: 79%
“…The wavelength difference between ME and standard resorcinol is acceptable because ME is a crude extract, not a pure substance. The previous study also revealed the crystallinity degree of ME at 20.86%, and its melting or glass transition temperature at 111 °C (Santoso et al 2014). All identifications indicated that ME consisted mostly of phenolic compounds, especially 1,3-benzenediolresorcin, commonly called resorcinol.…”
Section: Uv-vis Identificationmentioning
confidence: 73%
See 2 more Smart Citations
“…These adhesives are expensive and contain high levels of formaldehyde, and their availability will steadily decrease with time (Santoso et al 2014). Bio-adhesives that use renewable materials can substitute for synthetic adhesives in laminated composite manufacture.…”
Section: Introductionmentioning
confidence: 99%